Pengaruh Customer Experience Dan Trust Terhadap Repurchase Intention Di Daima Hotel Padang - Nadia Vega; Youmil Abrian (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
This research is motivated by guests who do not recommend Daima Hotel Padang due to their less satisfactory experience during their stay. The research aims to determine the influence of customer experience and trust on repurchase intention at Daima Hotel Padang. The research type is quantitative descriptive. using purposive sampling technique, a sample 0f 98 respondents who met the criteria of having stayed at least once at Daima Hotel Padang. Data collection was conducted using a questionnaire based on a Likert scale, which has been tested for validity and reliability. The data were analyzed using multiple linear regression and met the classical assumptions. After hypothesis testing, a coefficient of determination (R Square) value 0,051 was obtained, indicating that the variable of customer experience and trust influence repurchase intention by 51% with the remaining 49% influenced by others factors.